2016
DOI: 10.1097/md.0000000000005306
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alprostadil on preventing contrast-induced nephropathy for percutaneous coronary intervention in diabetic patients

Abstract: Background:At present, there are a lot of research about the effect of Alprostadil on preventing contrast-induced nephropathy for percutaneous coronary intervention (PCI) in diabetic patients, but the clinical efficacy is not consistent, so we conduct this study and therefore determine the dominant strategy for the treatment of PCI in diabetic patients based on the best evidence currently.Methods:An electronic database search was conducted in MEDLINE, Embase, Cochrane library, CBM, CNKI, VIP, and WanFang to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Zhang et al conducted a randomized controlled clinical trial involving 120 patients with coronary heart disease combined with diabetic mellitus undergoing coronary artery intervention therapy and indicated that alprostadil could significantly improve eGFR and effectively prevent the occurrence of CIN in such people. Similarly, in the diabetes mellitus subgroup analysis of the present study, it was also confirmed that the effect of alprostadil on the prevention of CIN was more beneficial in the patients with diabetes mellitus (OR = 0.26, 95% CI = 0.10–0.65, P = 0.003).A recently published meta‐analysis, involving 969 patients with diabetes mellitus undergoing PCI, also demonstrated that alprostadil could significantly decreased the incidence of CIN and adverse reactions . Therefore, alprostadil may become a promising candidate for prevention of CIN.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Zhang et al conducted a randomized controlled clinical trial involving 120 patients with coronary heart disease combined with diabetic mellitus undergoing coronary artery intervention therapy and indicated that alprostadil could significantly improve eGFR and effectively prevent the occurrence of CIN in such people. Similarly, in the diabetes mellitus subgroup analysis of the present study, it was also confirmed that the effect of alprostadil on the prevention of CIN was more beneficial in the patients with diabetes mellitus (OR = 0.26, 95% CI = 0.10–0.65, P = 0.003).A recently published meta‐analysis, involving 969 patients with diabetes mellitus undergoing PCI, also demonstrated that alprostadil could significantly decreased the incidence of CIN and adverse reactions . Therefore, alprostadil may become a promising candidate for prevention of CIN.…”
Section: Discussionsupporting
confidence: 85%
“…Koch et al [19] first explored the preventive effect of alprostadil on CIN in patients with renal impairment (SCr 1.5 mg/dl) and found that SCr in the alprostadil group was significantly lower than that in the placebo group after contrast administration. In our subgroup analysis, alprostadil showed a beneficial prophylactic effect in patients with eGFR 60 ml/ [20]. Therefore, alprostadil may become a promising candidate for prevention of CIN.…”
Section: Discussionmentioning
confidence: 63%
“…The data on the protective effects of several agents, such as trimatizidine [ 123 , 124 ], theophylline [ 95 , 125 127 ], alprostadil [ 128 , 129 ], nebivolol [ 130 ], fenoldopam [ 131 ] and iloprost [ 132 ], is not conclusive and does not support recommending their use to reduce the risk of PC-AKI.…”
Section: Resultsmentioning
confidence: 99%
“…Percutaneous coronary intervention (PCI) is the most effective means in the treatment of ACS in the world. [ 1 ] In recent years, with the development of clinical diagnosis and interventional therapy, the dose of contrast agent in PCI is increasing, and PCI can lead to contrast-induced nephropathy (CIN). Therefore, CIN has become a common complication of PCI, and has become the third leading cause of acute renal failure in hospital.…”
Section: Introductionmentioning
confidence: 99%